MUSICALITY OF A LITERARY WORK AND TRANSLATION ISSUE - Liubov I. Semerenko; Olexander O. Pliushchai (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2019)
The paper is aimed at clarifying the interpretation of the notion “musicality” of a literary work, both prose and poetic in literary studies; the notion of translation of poetry in translation studies and different approaches to poetry translation. An attempt has been made to evaluate the translator’s gains and losses in reproducing musicality of a poetic work. The translation of Anna Akhmatova’s poem “Creativity” (into English) by John Woodsworth has been analysed and taken as an example of translator’s fidelity to semantic meaning, sound and imagery of the original. The article is devoted to the study of musicality of a literary work and translation issue. It is stated that musicality of a literary work means its similarity with certain principles, formal peculiarities or expressive means which are characteristic of music. Music and literature have coexisted since ancient times and they have fundamental similarity in form. Unlike the visual arts which exist in space, music and literature are primarily temporal in nature. According to some scholars, music and literature arose as a single tradition of oral storytelling accompanied by music. Exploring musico-literary interactions it is stated that both systems, language and music, have some shared characteristics, despite their differences. In works that combine words and music, such shared characteristics can activate a process of exchange. On the one hand, the presence of sound means we often become aware of the sonic, material and abstracted form of words. On the other hand, the presence of works, with their strong capacity for reference, highlights the referential potentialities of sound. Three types of interaction of literature and music has been distinguished by Stephen Paul Scher, namely, literature in music (so-called program music, music plus literature, any vocal music) and music and literature. Music has inspired many writers and poets and many works of emotive prose and poetry are based on musical compositions and subjects. Music and musical performance often appear as elements of plot, setting, characters. Music is an integral part of the artistic world of many literary works. Using music, the author can introduce the events and characters into a particular cultural context and create a specific emotive effect. Musicality is considered to be a variety of intermediality, the process of interaction of various media, in a narrow sense, of different kinds of art; it is directly connected with the notion of intertextuality. Any works of art can be regarded as a text and comparison can be made of literature and painting visual representation, as defined by Hefferman, the verbal representation of painting in cinema, literature and architecture. The phenomenon of musicality of literary works, so-called musical literary texts, and intertextual correlations have been examined in literary studies and by the theorists of intertextuality. Trying to capture different links between literary and music, many scholars have explored the relationship between them and the interaction of the two arts. And now “music and word studies” is a popular field of research in an interdisciplinary academic world.